PENGARUH TEMPER TANTRUM TERHADAP PERUBAHAN PERILAKU DAN PSIKIS PADA ANAK USIA DINI - Lailiyah, Hilma Wahidatul; Nisa, Zahrotun; Nisfa, Nia Lailin (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
The effect of temper tantrums on children's psychological development. The purpose of this study was to determine the effect of temper tantrums and parenting styles on the impact of changes in child psychology. This type of research is Library research. The results of research analysts show that permissive parenting can help control in influencing changes in children's emotional behavior significantly than parenting in democratic or authoritarian forms. Changes in patterns of adaptation of gesture expressions positively or negatively The results of research studies explain the process of psychological control in early childhood emotional behavior including ignoring, gradually. The results of the analysis related to the impact of changing children's behavior include learning to control their own anger, learning to divert attention, training children's discipline, helping to find children's problems, avoiding embarrassing children, teaching about levels of anger, maintaining open communication, teaching how to be aware of their actions. Suggestions for parental research can understand and study phase changes in carrying out life challenges in children. If the child's psychiatric conditions such as frustration, fear, sadness and depression will be passed by the child more broadly.